Situation Report: Bulgaria, 17 July 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Aspects of Bulgarian-Yugoslav Relations Georgi Chankov Appointed Ambassador to Belgium and Luxembourg New Customs Rates on Passenger Cars Decree on the Development of Backward Districts Adopted Measures against Alcoholism and Narcomania in Bulgaria